Measuring local government performance in Malaysia: political indicators versus organizational theory / Zaherawati Zakaria - Zakaria, Zaherawati (2010)
There are localities in Malaysia where local government performance is systematically superior and others where it is inferior. Similar institutions perform systematically better here than there always opens up queries and objection among people. Recognizing the enormous practical implications of this question for local democratic governance in Malaysia, this paper aims on the decision-makers and researchers to assess and explain local government performance. Thus, this paper try looking forward the concept of local government performance and uses a wide variety of variables to gauge its variance on the one hand, and its roots in economic, political, legal, cultural and social factors on the other.